Decorations in Islam: In the Perspective of The Holy Quran And the Prophet of Hadith - Eblao, Amira Mohamed Khalifa; Abdul Hamid, Ahmad Faisal Faisal (Journal Al-Muqaddimah, 2017)
A lot of works was interested in about the Islamic art and most of them were dealt with two aspects. The first one concerns the types and fields that this art includes and the second one concerns the eras in which it established according to a specific historical sequence. Therefore, this study attempts to explore the extent of the relationship between the plant decorations and the geometrical Islamic decorations, firstly from the perspective of the Holy Quran and secondly from the Hadith of the Prophet. Thus, we will address the following points, the foundations the Islamic decorative art in the Holy Quran and in the Prophetic Hadith, the origins of the Islamic decoration and some properties that Islamic religion called that have relation to the art. Through the historical and the descriptive approach, we conduct the third aspect of this study. The finding was that the Islamic decorative art was closely related to what was mentioned in the Holy Quran and Hadith of the Prophet. It has a characteristic that distinguishes it from the rest of the other arts.